Analisis Mineralogi dan Kimia Bentonit Daerah Bone Bolango, Provinsi Gorontalo - Sufriadin Sufriadin; Purwanto Purwanto; Nanda Pratiwi Rapele; Chairil Sastria; Shany Sofiah Fauth (Jurnal Geomine, 2020)
Bentonite is one of industrial mineral deposit that has many applications in industries. In order to optimize its utilization, it is needed an initial assessment about the quality in particularly mineralogical and chemical composition. The objective of this study was to analyze mineralogical and chemical properties of bentonite samples from Bone Bolango Area, Gorontalo Province. Mineralogical analysis was performed by means of microscopic and X-ray diffraction (XRD) methods while chemical composition was determined by X-ray fluorescence (XRF) spectrometry. Results of analysis show that bentonite samples were composed of smectite mineral of montmorillonite type with the impurities constitute of plagioclase, quartz, calcite and maghemite. Chemical composition of Bone Bolango bentonite is dominated by SiO2 and Al2O3with the ratio in the range between 1.38 and 1.68. This bentonite was formed by weathering process of volcanic rocks mainly derive from plagioclase alteration. Based on mineral and chemical compositions, Bone Bolango bentonite is categorized as Ca-bentonite with relatively non-swelling property. However it is potentially used as raw materials in ceramic making and as absorbent.